2004
DOI: 10.1111/j.1654-1103.2004.tb02272.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tolerance to herbivory for plant survival in a British grassland

Abstract: Question: Is plant capacity to regrow under different herbivore treatments related to herbivore increaser/decreaser plant status? Location: Grassland in Southeast England (GR 41/944691). Methods: A field experiment was established in order to understand the role of plant tolerance to herbivory in explaining the abundance of nine grassland species previously known as herbivore increasers or decreasers. Tolerance was measured as a plant's capacity to regrow after exposure to herbivores. The experiment was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…Some authors showed that plants in burned areas tended to show a greater proportion of flowering individuals (Brewer and Platt 1994;Menges and Quintana-Ascencio 2004). Grazing is known to delay flowering time, due to a general decreased reproductive output that reduces growth and flowering (Ehrlén 1997;del Val and Crawley 2004). In our study we observed that areas recently burned (B0) and burned 1 year before showed the highest number of reproductive individuals in comparison to the other areas (B2 and B+).…”
Section: Resprouting Capacitymentioning
confidence: 35%
“…Some authors showed that plants in burned areas tended to show a greater proportion of flowering individuals (Brewer and Platt 1994;Menges and Quintana-Ascencio 2004). Grazing is known to delay flowering time, due to a general decreased reproductive output that reduces growth and flowering (Ehrlén 1997;del Val and Crawley 2004). In our study we observed that areas recently burned (B0) and burned 1 year before showed the highest number of reproductive individuals in comparison to the other areas (B2 and B+).…”
Section: Resprouting Capacitymentioning
confidence: 35%
“…del Val and Crawley 2004). Our study shows that even species within the grass functional group may exhibit considerable differences depending on local environmental conditions, including indirect influences from neighbouring plant species (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Herbivory is a major selective pressure affecting plant physiology and plant fitness (Karban and Strauss 1993, Hulme 1996a, Bigger and Marvier 1998, plant community composition and succession (Brown 1985, Gibson et al 1987, Brown and Gange 1992, Hulme 1996b, del-Val and Crawley 2004, and plant evolution (Holeski et al 2010 and references therein). Since the capacity of plants to resist and/or tolerate herbivory is mediated by their functional characteristics (i.e., traits sensu Violle et al 2007), plant species differing in their traits can show large differences in rates of herbivory.…”
Section: Introductionmentioning
confidence: 99%